Comprehensive Overview of the Structure and Regulation of the Glucocorticoid Receptor - Vandevyver, Sofie; Dejager, Lien; Libert, Claude (Endocrine reviews, 2014)
Glucocorticoids are among the most prescribed drugs worldwide for the treatment of numerous immune and inflammatory disorders. They exert their actions by binding to the glucocorticoid receptor (GR), a member of the nuclear receptor superfamily. There are several GR isoforms resulting from alternative RNA splicing and translation initiation of the GR transcript. Additionally, these isoforms are all subject to several transcriptional, post-transcriptional, and post-translational modifications, all of which affect the protein's stability and/or function. In this review, we summarize recent knowledge on the distinct GR isoforms and the processes that generate them. We also review the importance of all known transcriptional, post-transcriptional, and post-translational modifications, including the regulation of GR by microRNAs. Moreover, we discuss the crucial role of the putative GR-bound DNA sequence as an allosteric ligand influencing GR structure and activity. Finally, we describe how the differential composition and distinct regulation at multiple levels of different GR species could account for the wide and diverse effects of glucocorticoids.